2017
DOI: 10.1155/2017/9692517
|View full text |Cite
|
Sign up to set email alerts
|

On Fluid and Thermal Dynamics in a Heterogeneous CO2 Plume Geothermal Reservoir

Abstract: CO 2 is now considered as a novel heat transmission fluid to extract geothermal energy. It can achieve both the energy exploitation and CO 2 geological sequestration. The migration pathway and the process of fluid flow within the reservoirs affect significantly a CO 2 plume geothermal (CPG) system. In this study, we built three-dimensional wellbore-reservoir coupled models using geological and geothermal conditions of Qingshankou Formation in Songliao Basin, China. The performance of the CPG system is evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 21 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…Crooijmans et al (2016) considered the impact of heterogeneity on energy extraction for a low-temperature geothermal doublet system. Permeability and porosity heterogeneity greatly affected CO 2 migration (Xu et al, 2017;Wang et al, 2019) and the produced water temperature and heat recovery (Li et al, 2019). Pandey et al (2015) showed the influence of reservoir permeability heterogeneity during geothermal heat extraction.…”
Section: Parametersmentioning
confidence: 99%
“…Crooijmans et al (2016) considered the impact of heterogeneity on energy extraction for a low-temperature geothermal doublet system. Permeability and porosity heterogeneity greatly affected CO 2 migration (Xu et al, 2017;Wang et al, 2019) and the produced water temperature and heat recovery (Li et al, 2019). Pandey et al (2015) showed the influence of reservoir permeability heterogeneity during geothermal heat extraction.…”
Section: Parametersmentioning
confidence: 99%
“…When the fluids flow through the aquifer, it may give priority to the high porosity and permeability zone. As for the above thermophysical parameters of the reservoir, the permeability and porosity have the largest effect on flow field and heat extraction [32]. Therefore, permeability and porosity are considered as the main variables to study the heterogeneity effects.…”
Section: Heterogeneity Implementationmentioning
confidence: 99%
“…Here, we chose T2Well simulator to simultaneously calculate the flow in both the wellbore and in the reservoir; this simulator was developed by Pan and Oldenburg (2014) to solve the problem of nonisothermal flows in an integrated wellbore-reservoir system; it has been verified against an analytical solution of steady-state two-phase flow and field CO 2 production test data. In the recent years, T2Well has been widely applied for productivity forecasting of geothermal doublet systems (Feng et al., 2017; Li et al., 2019; Xu et al., 2017) and the interpretation of production tests in geothermal wells (Vasini et al., 2018).…”
Section: Introductionmentioning
confidence: 99%